EPI Receptor within the Ventrolateral Periaqueductal Grey Controls Thermonociception and Rostral Ventromedial Medulla Cell Activity in Healthy and Neuropathic Rat. Issue 1 (24th October 2011) - Palazzo, Enza; Guida, Francesca; Gatta, Luisa; Luongo, Livio; Boccella, Serena; Bellini, Giulia; Marabese, Ida; de Novellis, Vito; Rossi, Francesca; Maione, Sabatino
The aim of this study was to investigate the expression of prostaglandin EP 1 receptor within the ventrolateral periaqueductal grey (VL PAG). The role of VL PAG EP1 receptor in controlling thermonociception and rostral ventromedial medulla (RVM) activity in healthy and neuropathic rats was also examined. EP1 receptor was indeed found to be expressed within the VL PAG and co-localized with vesicular GABA transporter. Intra-VL PAG microinjection of ONO-DI-004, a selective EP1 receptor agonist, dose-dependently reduced tail flick latency as well as respectively increasing and decreasing the spontaneous activity of ON and OFF cells. Furthermore, it increased the ON cell burst and OFF cell pause. Intra-VL PAG prostaglandin E2 (PGE2) behaved similarly to ONO-DI-004. The effects of ONO-DI-004 and PGE2 were antagonized by intra-VL PAG L335677, a selective EP1 receptor antagonist. L335677 dose-dependently increased the tail flick latency and ongoing activity of the OFF cells, while reducing the ongoing ON cell activity. It also decreased the ON cell burst and OFF cell pause. In neuropathic rats using spare nerve injury (SNI) of the sciatic nerve model, EP1 receptor expression decreased in the VL PAG. However, ONO-DI-004 and L335677 were able to alter pain responses and ON and OFF cell activity, as they did in healthy animals. Collectively, these data show that within the VL PAG, EP1 receptor has a facilitatory effect on the nociceptive response and consistently affects RVM neuron activity. Thus, the blockade of EP1 receptor in the VL PAG leads to antinociception in neuropathic pain conditions, despite its down-regulation. The expression of EP1 receptor on GABAergic neurons is consistent with an EP1 receptor blockade-induced disinhibition of the antinociceptive descending pathway at VL PAG level.